Potentiometric studies on the complexation of copper(II) by phenolic acids as discrete ligand models of humic substances - Borges, Fernanda (2019)
Studies on the complexation of copper(II) by phenolic acids, as ligand models of humic substances were done by potentiometry. The acids under study were: 3,4-dihydroxyhydrocinnamic acid or hydrocaffeic acid (1), 3,4-dihydroxyphenylacetic acid (2) and 3,4-dihydroxybenzoic acid or protocatechuic acid (3). Acidity constants of the ligands and the formation constants of metal-ligand complexes were evaluated by computer programs. The carboxylic group of the phenolic acids has different pK(a1) values, being the dissociation constants intrinsically related with the distance between the function and the aromatic nucleus. The results obtained allow concluding that acidity constants of the catechol moiety of the compounds are similar with pK(a2) and pK(a3) values between 9.47-9.41 and 11.55-11.70. The complexation properties of the three ligands towards copper(II) ion are quite similar, being the species found not different either in nature or stability. Although the model ligands have some structural differences no significant differences were found in their complexation properties towards copper(II). So, it can be postulated that complexation process is intrinsically related with the presence of a catechol group.